Survei Kejadian Growth Faltering Pada Anak Usia 6–12 Bulan di Kota Pekanbaru - Syeptri Agiani Putri; Riri Novayelinda; Ririn Muthia Zukhra; Yesi Hasneli (Malahayati Nursing Journal, 2025)
ABSTRACT Growth faltering is a condition of growth failure characterized by a slowing growth rate. The main cause is malnutrition. Continuous growth faltering conditions can cause disturbances in growth, cognitive and psychomotor development, physical activity, behavior and learning abilities. The Purpose of this study is to see the incidence of growth faltering in children aged 6 – 12 month in Pekanbaru City. This study uses a quantitative descriptive method with cross sectional approach. The research sample was 386 children aged 6 - 12 months using the Lemeshow formula. The sampling technique used purposive sampling. The instruments used were demographic data questionnaires and anthropometric measuring instruments. The data analysis used was univariate analysis. The research results show that the incidence of growth faltering in children aged 6 - 12 months in Pekanbaru City is 42.7%. Characteristics of children with growth faltering occur in children aged 9 - 11 months (40.3%) and male (51.5%). The majority of respondents were born at full term (39.9%), not LBW (43%), had a history of receiving exclusive breastfeeding (44.7%) and had family income above the minimum wage (44.9%). Based on the research results, it is recommended that the Community Health Center add education regarding providing appropriate and healthy MPASI before giving MPASI to children. Suggestions for future researchers to be able to identify factors related to the incidence of growth faltering in children. Keywords: Growth Faltering, Malnutrition, Stunted  ABSTRAK Growth faltering merupakan suatu kondisi gagal tumbuh yang ditandai dengan melambatnya laju pertumbuhan. Penyebab utamanya adalah kekurangan gizi. Kondisi growth faltering yang terus menerus dapat menyebabkan gangguan pada pertumbuhan, perkembangan kognitif dan psikomotorik, aktivitas fisik, perilaku dan kemampuan belajar. Tujuan penelitian ini adalah untuk melihat kejadian growth faltering pada anak usia 6 – 12 bulan di Kota Pekanbaru. Penelitian ini menggunakan metode deskriptif kuantitatif dengan pendekatan cross sectional. Sampel penelitian sebanyak 386 anak usia 6 – 12 bulan dengan menggunakan rumus Lemeshow. Teknik pengambilan sampel menggunakan purposive sampling. Instrumen yang digunakan adalah kuesioner data demografi dan alat ukur antropometri. Analisis data yang digunakan adalah analisis univariat. Hasil penelitian menunjukkan bahwa kejadian growth faltering pada anak usia 6 – 12 bulan di Kota Pekanbaru sebesar 42,7%. Karakteristik anak dengan growth faltering terjadi pada anak usia 9 – 11 bulan (40,3%) dan berjenis kelamin laki-laki (51,5%). Mayoritas responden lahir cukup bulan (39,9%), tidak BBLR (43%), memiliki riwayat mendapat ASI eksklusif (44,7%) dan memiliki pendapatan keluarga di atas UMR (44,9%). Berdasarkan hasil penelitian disarankan kepada Puskesmas untuk menambah edukasi mengenai pemberian MPASI yang tepat dan sehat sebelum memberikan MPASI pada anak. Saran bagi peneliti selanjutnya agar dapat mengidentifikasi faktor-faktor yang berhubungan dengan kejadian growth faltering pada anak. Kata Kunci: Gizi Buruk, Growth Faltering, Stunting.